2021
DOI: 10.1002/admi.202100142
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Burgeoning Optical Sensors with Ultra‐Precision Hierarchical Structures Inspired by Butterflies

Abstract: In recent years, there has been an increasing interest in the novel bioinspired sensors, especially for their selectivity, response time, and sensitivity. Particular attention is paid to the novel optical functional materials that are crucial for the sensors to achieve various energy transduction. Ideally, many critical parameters of the optical sensing materials can be appropriately tailored to meet various specific requirements using optimal design. Over a long and cruel evolution, nature's creatures have cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 79 publications
0
5
0
1
Order By: Relevance
“…Розвиток сучасних технологій, що ґрунтуються на якісно нових принципах (оптоволоконні сенсори, наноструктури, органічні напівпровідники та перетворювачі енергії) вимагає пошуку нетрадиційних матеріалів, які не тільки задовольняли б вимоги сучасної техніки, але були б доступними за собівартістю. Цим вимогам повністю відповідають рідкокристалічні композити [8], які можна одержати на основі холестеричних та нематичних рідких кристалів. Рідкі кристали (РК) використовуються для створення сенсорів хімічних речовин [9], температури [10], вологості [11], парів шкідливих речовин [12] тощо.…”
Section: Orcid: 0000-0002-9101-3768unclassified
“…Розвиток сучасних технологій, що ґрунтуються на якісно нових принципах (оптоволоконні сенсори, наноструктури, органічні напівпровідники та перетворювачі енергії) вимагає пошуку нетрадиційних матеріалів, які не тільки задовольняли б вимоги сучасної техніки, але були б доступними за собівартістю. Цим вимогам повністю відповідають рідкокристалічні композити [8], які можна одержати на основі холестеричних та нематичних рідких кристалів. Рідкі кристали (РК) використовуються для створення сенсорів хімічних речовин [9], температури [10], вологості [11], парів шкідливих речовин [12] тощо.…”
Section: Orcid: 0000-0002-9101-3768unclassified
“…In 2007, Potyrailo et al measured the reflectance spectra of the Morpho sulkowskyi butterfly and found that its iridescent scales could produce different optical responses to individual vapors such as water, methanol, ethanol, and isomers of dichloroethylene . This work inspired several follow-up studies. These nontraditional detection schemes demonstrate the potential to identify different gases in a complex sample mixture. However, these designs usually require a relatively large amount of analyte to generate the output signal with a sufficient signal-to-noise ratio, resulting in an inferior limit of detection (LoD) compared to detectors based on traditional electrical readout methods.…”
Section: Introductionmentioning
confidence: 99%
“…Many natural organisms exhibit structural circularly polarized colors and iridescent appearance instigated by periodic and ordered nanostructures of helical type. Natural colored materials often reconcile multiple functional properties, such as high strength and toughness and bright iridescence such as those observed in butterflies, [2][3][4][5] beetles, [6][7][8] plants, [9][10][11][12] and opal. [13][14][15][16][17] Optical chirality was discovered in 1848 by the French scientist, Louis Pasteur.…”
Section: Introductionmentioning
confidence: 99%